An optimal dispatch model of power economic load system based on modified bat algorithm. (18th August 2018) - Wu, Zhigong; Wang, Yunhu
Abstract: The Economic load dispatch (ELD) problem considering valve-point effects, power balance constraint and the generating capacity constraint is a high-dimensional, discontinuous, non-differentiable, non-convex and nonlinear optimization problem, which cannot be solved by classical mathematics methods. In order to solve the problem, this paper presents a modified Bat Algorithm (MBA). Via simulating echolocation behavior of bats, the algorithm gets the optimal solution in the solution space. To enhance the overall performance and effectiveness of the proposed algorithm, the noninertia weight and hybrid mutation operation are integrated with the proposed method. To verify the effectiveness of the proposed method, the 3-unit test system, 13-unit test system and 40-unit test system were carried on the test. The simulation results obtained by the proposed algorithms are compared with the results using other recently developed methods which are available in the literature. From numerical results, it is found that the proposed MBA with noninertia weight and hybrid mutation operation approach is able to provide the better solution than other reported techniques in terms of fuel cost.